Linear optimization model for fish processing production planning - Elín Helga Jónsdóttir 1990- (2017)
The fishing industry feature a fast paced and ever-changing environment wherein recent years major developments of high-tech equipment’s have occurred in the processing sector resulting in a wider range of product possibilities as well as increasing production capacity. This paper attempts to show that optimization model and sensitivity analysis can be beneficial as a decision making tool for production manager in this fast paced environment. The paper proposes a linear optimization model that can be used as a decision aid for one-day production planning. The Net Profit Contribution is maximized subject to raw material requirements, machine time requirements, orders, and contracts. The model was tested and validated using real data from a typical processing day at a vertically integrated fishery in Iceland. Keywords: Linear programming, Product mix, Production planning, Fish processing Sjávarútvegur einkennist af hröðu og síbreytilegu umhverfi þar sem mikil þróun hátæknibúnaðs hefur átt sér stað undanfarin ár og áratugi í fiskvinnslunni, sem skilað hefur aukinni afkastagetu tækja og auknu vöruúrvali. Í þessari ritgerð er gerð tilraun til þess að sýna fram á notagildi bestunar og næmnigreiningar við ákvörðunartöku í framleiðslu fiskvinnslu. Línulegt bestunarlíkan fyrir daglega áætlanagerð í fiskvinnslu er sett fram og sýnt er fram á notkunarmöguleika líkansins til aðstoðar við ákvörðunartöku. Framlegð fiskvinnslunnar er hámörkuð með tilliti til hráefnis, véltíma, pantana og samninga. Líkanið var prófað í íslensku sjávarútvegsfyrirtæki og var byggt á raungögnum frá dæmigerðum vinnsludegi. Lykilorð: Línuleg bestun, afurðarsamsetning, áætlanagerð, fiskvinnsla